Analisis Efektivitas E- Learning Di Tengah Pandemi Covid-19 - Hadiqoh Asmuni (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Abstract The impact of Covid-19 affects psychological conditions and changes in the lifestyle of human behavior over a longer period of time.This has an impact on education in Indonesia. Lecturers, teachers and students must familiarize themselves with long-distance learning (PJJ). Almost all campuses in Indonesia apply the WFH (Work From Home) policy for lecturers / employees, and study from home for students as well as the STIB Banyuwangi campus. This study aims to analyze e-learning activities during the Covid-19 pandemic.This study used a qualitative approach using descriptive methods in which the informants consisted of lecturers and students in the Islamic Religious Education Study Program. Based on the results of the research, it can be concluded that the learning process during the Covid-19 pandemic in the Islamic religious education department through virtual applications in the form of: meet google, zoom, telegram, youtube, teamlink, messenger, google classroom, whatsapp.Online implementation is fairly smooth, though less than ideal. The evaluation of student learning outcomes varies, from very unsatisfactory to good. There are several obstacles that are felt by students and lecturers in virtual learning, including: insufficient internet quota, unstable signal networks, and media such as androids and laptops.Online learning has indeed become one of the steps considered effective during the Covid-19 pandemic, but it also requires learning models and teaching materials that are easily understood by using more varied applications to make them attractive if used in the long term.